2017
DOI: 10.1039/c7fo00654c
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyperlipidemic effect of rice bran polysaccharide and its potential mechanism in high-fat diet mice

Abstract: Hyperlipidemia occurs very often in modern society along with a high calorie intake and is regarded as one of the greatest risk factors for the prevalence of cardiac vascular disease (CVD). In this study, we investigated the anti-hyperlipidemic effect of the rice bran polysaccharides (RBP) and its mechanism in a high fat diet animal model. 60 ICR mice were randomly divided into 3 groups, which included Control, HFD (high fat diet) and HFD + RBP, and each group included 20 mice. The control group was fed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 49 publications
1
64
0
Order By: Relevance
“…In the cosmetics industry, it is currently being used as facial masks or ointments and also in food products, accompanied with other components to treat skin disease as well as help in activation of blood circulation [3]. Presently, the replacement of synthetic antioxidant with naturally occurring antioxidant is increasing due to the side effects associated with synthetic antioxidant such as increased risk of cancer [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the cosmetics industry, it is currently being used as facial masks or ointments and also in food products, accompanied with other components to treat skin disease as well as help in activation of blood circulation [3]. Presently, the replacement of synthetic antioxidant with naturally occurring antioxidant is increasing due to the side effects associated with synthetic antioxidant such as increased risk of cancer [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Since the effects of cigarette smoking on LDL-C levels has not reached to the crucial conclusions, [2][3][4][5][6][18][19][20][21] in the current study, as mentioned above, we tested the hypothesis that whether CSE affects the target genes associated with metabolic pathway of LDL-C. Even though our epidemiological observation made us quite clear, there has been several reports depicting that smoking habit elevated LDL-C in epidemiology investigations.…”
Section: Discussionmentioning
confidence: 78%
“…Even though our epidemiological observation made us quite clear, there has been several reports depicting that smoking habit elevated LDL-C in epidemiology investigations. [18][19][20][21] Thus, by using quantitative RT-PCR, we examined whether CSE affects the expression of genes (such as PPARα, PPARβ/δ, PPARγ, ATP-binding cassette, subfamily A transporter 1(ABCA1), PGC1a, PGC1b, SREBP1a, SREBP1c, SREBP2, Fatty acid synthase (FASN), acetyl-CoA carboxylase (ACC), sirtuin (SIRT), CD36, FOXO1, STAT5B, Liver X receptor (LXR) α, LXRβ, Farnesoid X receptor (FXR), vitamin D receptor, hydroxymethylglutaryl-CoA (HMG-CoA) reductase, and uncoupling protein (UCPs)), associated with LDL-C metabolism in HepG2 cells 22) (data not shown except Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that Scu decreased lipid accumulation occurred by reducing the level of TG in PA‐treated HepG2 cells. Moreover, Fasn regulates the synthesis and degradation of TG, ACC is the rate‐limiting enzyme for fatty acid synthesis, and CD36 is a fatty acid transporter that promotes lipid uptake by the cells (Nie et al, ). PA incubation increased the mRNA expression levels of Fasn, ACC, and CD36.…”
Section: Resultsmentioning
confidence: 99%